2009
DOI: 10.1158/0008-5472.sabcs-09-2123
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Pathway Activation in Breast Cancer Is Associated with the Basal-Like Phenotype and Cancer-Specific Mortality.

Abstract: Background: Current biological therapies for breast cancer are tailored to steroid hormone (ER, PR) and HER2 receptor status. Understanding the biological basis of resistance to current targeted therapies and the identification of new potential therapeutic targets is an ongoing challenge. The PI3K pathway is altered in a high proportion of breast cancers and may be associated with specific phenotypes and therapeutic resistance. We undertook an integrative study of mutational, copy number and expression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
77
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 0 publications
5
77
0
2
Order By: Relevance
“…In contrast, complete loss of PTEN was more frequent in ER2 than ER1 tumors (7/19 vs. 12/116, p50.006), consistent with a recent report. 6 HER2 overexpression and complete loss of functional PTEN were not identified in the same tumor in this study, which is consistent with a previous report 22 which found no PTEN point mutations in HER2 overexpressing tumors, but in contrast to other studies which identified both HER2 overexpression and reduced or absent PTEN expression in 4% of their cohorts. 6,8 Therefore complete loss of PTEN and HER2 overexpression appear to be rarely present in the same tumor suggesting that each of these events activate the PI3K pathway sufficiently to not require additional alterations affecting this pathway.…”
Section: Pten Loss Of Function Can Be Accurately Identified By Ihc Ansupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, complete loss of PTEN was more frequent in ER2 than ER1 tumors (7/19 vs. 12/116, p50.006), consistent with a recent report. 6 HER2 overexpression and complete loss of functional PTEN were not identified in the same tumor in this study, which is consistent with a previous report 22 which found no PTEN point mutations in HER2 overexpressing tumors, but in contrast to other studies which identified both HER2 overexpression and reduced or absent PTEN expression in 4% of their cohorts. 6,8 Therefore complete loss of PTEN and HER2 overexpression appear to be rarely present in the same tumor suggesting that each of these events activate the PI3K pathway sufficiently to not require additional alterations affecting this pathway.…”
Section: Pten Loss Of Function Can Be Accurately Identified By Ihc Ansupporting
confidence: 92%
“…6 HER2 overexpression and complete loss of functional PTEN were not identified in the same tumor in this study, which is consistent with a previous report 22 which found no PTEN point mutations in HER2 overexpressing tumors, but in contrast to other studies which identified both HER2 overexpression and reduced or absent PTEN expression in 4% of their cohorts. 6,8 Therefore complete loss of PTEN and HER2 overexpression appear to be rarely present in the same tumor suggesting that each of these events activate the PI3K pathway sufficiently to not require additional alterations affecting this pathway. Similarly, PIK3CA mutations were identified in combination with either HER2 overexpression or PTEN complete loss in only four tumors in this study thus multiple alterations in this pathway are predominantly mutually exclusive as has been previously described.…”
Section: Pten Loss Of Function Can Be Accurately Identified By Ihc Ansupporting
confidence: 92%
See 3 more Smart Citations